Como vivir juntos : Selección 27a Bienal de São Paulo = How to live together : A selection of the 27th Bienal de São Paulo. - Brugnoli, Francisco; Cohen, Ana Paula; Costa, Helouise; Coutinho, Cristovão; Duarte, Luisa; Erdemci, N. Fulya; Freire, Cristina; Garcia Navarro, Santiago; Groos, Ulrike; Hanru, Hou; Lagnado, Lisette; Leighton, Tanya; et al. (Santiago de Chile : MAC - Museo de Arte Contemporaneo Santiago de Chile, 2007)
Abdessemed, Adel ; Abdul, Lida ; Alvarado, Narda Fabiola ; Andrade Tudela, Armando ; Cardoso, Ivan ; Faust, Jeanne ; Ferrari, León ; Gladwell, Shaun ; Hernández, Diango ; Hugo, Pieter ; Jodice, Francesco ; Kratsman, Miki ; Long March Project ; Lopes, Jarbas ; Matta-Clark, Gordon ; Melo, Hélio ; Mendieta, Ana ; Navarro, Mario ; Ortega, Fernando ; Patricio, Martinho ; Potrc, Marjetica ; Shibli, Ahlam ; Shimabuku ; Song Sanghee ; Superflex ; Visser, Barbara
geboorteplaats en -datum per kunstenaar
Portugees
Spaans
Engels
Exhibition. Como vivir juntos : Selección 27a Bienal de São Paulo = How to live together. MAC - Museo de Arte Contemporaneo Santiago de Chile, 27.04.2007 - 01.07.2007.
boek